2010
DOI: 10.3136/fstr.17.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long Low Temperature-Short High Temperature Cooking Cycle on Physicochemical Properties of Beef

Abstract: A two-step heating process, long low temperature-short high temperature cooking cycle, is used to maximize fat reduction in roast beef. First, the beef was cooked at a low temperature for a long time; then, it was cooked at a higher temperature for a short time. The study examines cooking loss, fat content, texture, and inosine 5'-monophosphate (IMP) production of cooked meat under different heating conditions. In an oven, the internal temperature of the meat increased to a transition point of 48 or 54℃ at ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…Thermal processing of food is defined as the delivery of heat to the products. Increment in temperature can be achieved by heat transfer through conduction (Kerth et al, 2003), convection (Kondjoyan et al, 2006;Ko et al, 2011) and radiation (Shilton et al, 2002). Traditionally, food is heated by conduction and/or convection.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal processing of food is defined as the delivery of heat to the products. Increment in temperature can be achieved by heat transfer through conduction (Kerth et al, 2003), convection (Kondjoyan et al, 2006;Ko et al, 2011) and radiation (Shilton et al, 2002). Traditionally, food is heated by conduction and/or convection.…”
Section: Introductionmentioning
confidence: 99%
“…Protein denaturation reduces water holding capacity, shrinks muscle fibers, and causes connective tissue degradation, subsequently leading to a harder texture [Ovissipour et al, 2013]. The denaturation of actin and myofi brillar proteins decreases tenderness, while the gelatinization of connective tissue makes the meat tender again [Sanghoon et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…No differences related to cooking method were found in cooking yields. However, Ko et al (2011) found greater cooking loss in a two-step oven heating process (long low temperature and finishing with short high temperature) than conventional forced-air convection oven in beef LL.…”
Section: Discussionmentioning
confidence: 86%
“…Some researchers (Powell et al 2000;Jeremiah and Gibson 2003;Ko et al 2011) have investigated cooking protocols (i.e., braising, holding, etc.) within forced-air convection ovens to fixed or variable end point temperatures.…”
Section: Discussionmentioning
confidence: 99%